Welfare, development, and cost-efficiency: A global synthesis on incentivizing energy efficiency measures through co-benefits. (July 2022) - Chatterjee, Souran; Rafa, Nazifa; Nandy, Ananya
Abstract: Energy efficiency measures (EEMs) can serve as promising policy tools to lower greenhouse gas (GHG) emissions by reducing energy demand. Besides climate benefits, EEMs can also generate various non-energy, non-climate, and local benefits, popularly known as multiple impacts (MI)/co-benefits. These MIs differ substantially across different socioeconomic contexts and play an important role in determining the uptake rate of EEMs in different parts of the world. By taking the European Union (EU) member states and South Asian countries as case studies, this paper uses a two-tier methodological approach to explore the diversity of MIs in regions with widely contrasting contexts. Findings of the study show that, for South Asia, energy savings and energy security are the most important MIs, whereas other MIs such as reduced air pollution and health benefits were also commonly highlighted co-benefits for both regions. Furthermore, the findings also show that, for South Asia, climate targets alone cannot accelerate the implementation of EEMs, and thus, the progress made in the targets of different Sustainable Development Goals as a consequence of the co-benefits of EEMs is an important incentive for EEM uptake in South Asian countries. The magnitude of the co-benefits of EEMs is significant for both regions, amounting to billions of dollars. By analyzing the magnitude and different contexts of the MIs, this paper identifies the existing barriers and key gaps for the quantitative evaluation of MIs. This assessment further helps in understanding how to overcome the barriers imposed by the socioeconomic contexts of the regions. Highlights: Multiple impacts (MIs) can encourage the uptake of energy efficiency measures (EEMs). MIs vary substantially across different socioeconomic contexts. MIs improve the cost-effectiveness of EEMs in the developed EU member states. Climate targets alone cannot facilitate the EEM uptake in the developing South Asia. SDGs delivered by MIs can encourage the uptake of EEMs in South Asian countries.